PENERAPAN STORYLINE TEMA THE KINGDOM UNDER THE SEA PADA AREA DISPLAY JAKARTA AQUARIUM - Intan, Intan; Mutiara, Maitri Widya; Pane, Sri Fariyanti (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2023)
Indonesia is a maritime country and the sea is one of the most important natural resources, but many Indonesian people are not aware of and do not care about the balance of the ecosystem. This resulted in marine life being threatened and extinct unnoticed. Oceanarium is a place of recreation and education, as well as a place of conservation that displays marine life in the aquarium. One of Oceanarium in Jakarta is the Jakarta Aquarium which is located inside the Neo Soho Mall. Jakarta Aquarium is one of the aquarium tours featuring various sea water biota in Indonesia. At this time there is a great need for an introduction to seawater biota. To create a fun and educative atmosphere, as well as present storyline good, appropriate interior design is needed and supports the Jakarta Aquarium by applying the concept of the theme